Relationship Between Invertase Enzyme Activities and Sucrose Accumulation in Sugarcane (Saccharum spp.) - Tana, Bootsarin; Chanprame, Sontichai; Tienseree, Nongluck; Tadakittisarn, Sukuntaros (Agriculture and Natural Resources, 2014)
The sucrose content, and the activities of sugar metabolism enzymes—namely, soluble acid invertase (SAI), neutral invertase (NI) and cell wall invertase (CWI), of various developmental stages of the stem and the relationships among them were investigated in cultivated sugarcane (Saccharum officinarum L.), line 20-2248 and wild sugarcane S. spontaneum, line S98-244. Stems of both sugarcane species 6–12 mth after planting (MAP) stems were collected and examined with samples consisting of three parts of the internode—the top, middle and bottom—representing relatively immature, maturing and mature internodes, respectively. The results showed that sucrose was the main sugar in the two species. Sugarcane stems of the two species revealed different patterns of sucrose accumulation and activities of invertase (SAI, CWI and NI). The sucrose content of line 20-2248 increased from 6 to 12 MAP and was highest in the bottom part and decreased in the middle and top parts, respectively, whereas the sucrose content of line S98-244 decreased from 6 to 12 MAP and was highest in the middle part than in the lower the bottom and top parts. The activities of SAI, CWI and NI in both sugarcane species were higher in the top part at each growth stage, lower in middle and lowest in the bottom part of the stem. These activities decreased from 6 to 12 MAP with line 20-2248, whereas the activities increased with increasing time after planting for line S98-244. There was a significantly negative correlation between the sucrose content and the activity of SAI, CWI and NI for line 20-2248. With line S98-244, the lowest concentration of sucrose was significantly negative only with SAI activity. The sucrose content correlation with CWI and with NI activity showed negative correlations but they were not significant.